Early Bronze Age Levantine Metal Weapons from the Collection of the Palestine Exploration Fund - Montanari, Daria (Palestine exploration quarterly, 2018)
Metal weapons found during the two historic excavations of Tell el-Hesi and Gezer carried out by W.M.F. Petrie, J.F. Bliss, R.A.S. Macalister, and Alan Rowe, on behalf of the Palestine Exploration Fund are here re-evaluated and compared in the light of recent discoveries. An in-depth study allowed some considerations about the connection existing between Southern Levantine 'urbanisation' and metal weapons, remarking the relation between such a kind of specimens and hoards, depots and funerary sets.